Paradigma Pendidikan Politik Antikorupsi dan Kesetaraan Gender di Partai Politik - Mirza Satria Buana; Erlina Erlina; Eka Yulia Rahman (Komisi Pemberantasan Korupsi, 2021)
Political education for women politicians is ineffective because women are still considered merely as an ‘object’ to perpetuate patriarchy political dynasty. This study utilizes a legal inter-diciplinary methodology. It selects five political parties. Respondents are female politicians who have experiences on political education, anti-corruption and gender equality issues. Most of political parties are dependent with political figure as a ‘strong leader’. Political education’s curriculum is a doctrinization of parties’ political figures. It lacks of anti-corruption and gender equality perspectives. Reform should start from within by changing its paradigm into member-based mass political party, so political education can leverage female politicians.